The Employment Effects of a Pandemic Wage Subsidy - Michael Smart; Matthew Kronberg; Josip Lesica; Danny Leung; Huju Liu (Center for Economic Studies and ifo Institute (CESifo), 2023)
We estimate the causal effects of a pandemic-era wage subsidy program in Canada on job losses and business closures. Our estimates use administrative microdata and a regression discontinuity strategy to estimate the effects of marginal changes in the wage subsidy rate. The estimated net wage elasticity of employment was 0.11, implying a small aggregate employment effect of the program and an estimated fiscal cost per job saved of nearly 200,000 per year. Subsidy payments caused a small but persistent reduction in business closure rates during subsequent waves of the pandemic, and increased earnings of existing employees. In all, our results suggest the subsidies did little to preserve job matches, but played a greater role in the overall social insurance response to the pandemic.
Keywords: H25; E32; 330; Canada emergency wage subsidy; Covid-19; incrementality